Pendampingan Literasi Digital Pada Generasi Milenial Sebagai Penguatan Moderasi Beragama - Shomad F.N, Ahmadi Abdul; Zatadini, Galuh Indah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The advent of digitalization has led to the emergence of numerous information disruptions, which have the potential to obfuscate the distinction between accurate and misleading information. The millennial generation is susceptible to exposure to invalid information, hoaxes, and radical content that has the potential to influence religious views. The objective of digital literacy is to facilitate the recognition, classification, and filtering of pertinent and reliable information, thereby fostering an environment of tolerance, inclusivity, and respect for diversity. The objective of this initiative is to cultivate a generation of millennials that are digitally adept and capable of becoming agents of peace in a multicultural society. The objective is to gain an understanding of religious teachings in a prudent manner, without being constrained by extremist ideologies, in order to reinforce the principles of religious moderation. This community service employs the Asset-Based Community Development (ABCD) method through the concept of empowerment as a people-centered participatory development effort, with the objective of imparting digital literacy skills to the millennial generation in order to reinforce religious moderation. The results of this service demonstrated a transformation in the knowledge and insights of the participants with regard to digital literacy and religious moderation. It is even possible to establish a millennial community that is concerned with digital literacy. As a result of this service, not only is a digital-savvy millennial generation created, but also one that is sensitive to religious issues and is able to play an active role in creating harmony between religious communities through the digital space.ABSTRAKMasifnya digitalisasi menciptakan berbagai disrupsi informasi yang menyamarkan mana informasi benar dan informasi yang menyesatkan. Generasi milenial menjadi kelompok rentan terhadap paparan informasi yang tidak valid, hoaks, dan konten radikal yang dapat memengaruhi cara pandang beragama. Literasi digital berupaya mengenali, memilah, dan menyaring informasi yang relevan dan bertanggung jawab, sehingga mampu membangun sikap toleransi, inklusivitas, dan menghargai keberagaman. Tujuan adanya pendampingan ini untuk menciptakan generasi milenial yang cerdas digital dan mampu menjadi agen perdamaian di masyarakat yang multikultural. memahami ajaran agama secara bijak tanpa terjebak ekstremisme sebagai strategi penguatan moderasi beragama. Pengabdian masyarakat ini menggunakan metode Asset Based Community Development (ABCD) melalui konsep pemberdayaan sebagai upaya pembangunan yang bersifat people-centered participatory dalam menambah skill literasi digital generasi milenial sebagai penguatan moderasi beragama. Hasil pengabdian ini menunjukkan adanya transformasi pengetahuan dan wawasan peserta terhadap literasi digital dan moderasi beragama. Bahkan kami dapat membentuk komunitas milenial peduli literasi digital. Dengan adanya pengabdian ini tidak hanya menciptakan generasi milenial yang cakap digital namun juga memiliki kepekaan terhadap isu-isu keagamaan serta mampu berperan aktif menciptakan harmoni antar umat beragama melalui ruang digital.